“Bathtubs Teeming with Frogs: Confluence of Form in the Multi-modal Work of Spanish Artist and Poet Margarita Merino” - Dean-Thacker, Veronica; Girard, Jack (Advances in Social Sciences Research Journal, 2018)
Not Available